Liquid phase dehydration of 1-indanol: Selective synthesis of indene over microporous acid catalysts - Bertero, Nicolas Maximiliano (2015)
The selective dehydration of 1-indanol in liquid-phase was studied at 363 K and 2 bar, over solid acid catalysts, and using cyclohexane as a solvent. Mesoporous SiO2-Al2O3 with a high density of strong Lewis acid sites produced di-1-indanyl ether and other heavy products apart from indene. In contrast, the overall selectivity to indene with beta zeolite (HBEA, Si/Al = 12.5), HZSM-5 (Si/Al = 20) and dealuminated mordenite zeolite (HMOR, Si/Al = 80) was almost 100%. The transition state shape selectivity and a moderate density of both Lewis and Brønsted acid sites were crucial to achieve high selectivity to indene. In spite of the high overall selectivity, the final yield in indene with HBEA was only 55%. This was attributed to the formation of heavy compounds inside the large cavities of HBEA, which cannot diffuse through its micropores. In contrast, yields in indene higher than 90% were obtained with HMOR and HZSM-5. It was also observed that the yield in indene increased with time even after reaching the 1-indanol total conversion, which indicates the slow diffusion of the reactant and product molecules inside of the microporous network of HMOR and HZSM-5. Therefore, a process involving liquid phase dehydration of 1-indanol, employing one of these two zeolites as a catalyst would provide: 1) high yield in indene; 2) easy separation of product from solvent; 3) easy separation of the catalyst from the reaction medium.